Vitamin-D Status in General Population of District Buner Khyber Pakhtoonkhwa (Journal of Pakistan Orthopaedic Association, 2023)
Background: Vitamin D is a fat-soluble vitamin. It has effects on almost all organs of the body. Vitamin D has many forms but vitamin D2 and vitamin D3 (cholecalciferol) are most important for human body.Objective: To determine the frequency of Vitamin D Deficiency in District Buner Khyber Pakhtoonkhwa.Material and Methods: This case series study was conducted from Jan 2019 to Jun 2020 at DHQ Hospital Daggar Buner. In this study 149 patients were selected randomly with age above 15 years. Patients with musculoskeletal pain, proximal myopathy, generalize body pain, non-traumatic bone tenderness, were included. A cut-off value of less than 8ng/dL was considered as deficient, between 20ng/dl to 30ng/dl as insufficiency and a value of more than 30ng/dl was sufficient. The data was collected with the help of a questionnaire and was put it into SPSS version 16 for analysis.Results: 115 were females and 34 were males. Out of 149 54 (36.2%) have sufficient, 25 (16.7%) have insufficient and 70 (47%) have deficient Vitamin D levels. The most common population were housewives (62%). 9.3% were with comorbidities (6% diabetic and 3.3% hypertensive). Highest proportions of the Vitamin D deficiency are observed in age groups of 10-19 years and 20-29 Years that is 83.5% and 58.5% respectively. While more than half of the age groups above 39 are Vitamin D sufficient. While in profession groups highest proportion is for the students followed by housewives that is 69% and 51% respectively.Conclusion: Almost every person in the District Buner is Vitamin D deficient until proven otherwise.